Anthropology of Nature - Philippe Descola (Collège de France, 2014)
It looks as though the anthropology of nature is an oxymoron of sorts, given that for the past few centuries, nature has been characterized in the West by humans' absence, and humans, by their capacity to overcome what is natural in them. But nature does not exist as a sphere of autonomous realities for all peoples. By positing a universal distribution of humans and non-humans in two separate ontological fields, we are for one quite ill equipped to analyse all those systems of objectification...